1977
DOI: 10.1159/000241012
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Brain Growth Stages: An Analytical Review

Abstract: Study of data in the literature on rat and mouse brain growth from birth to weaning reveals a stagewise growth in average brain weight. Rapid growth occurs in the intervals between days 0–6, 8–12, and 17–23 after birth. Slow growth periods then lie in the intervals 6–8, 12–17, and after 23 days. The first slow growth period is signalled by events occurring at its end: substantial acceleration of synthesis of RNA, DNA, protein, and myelin. The second slow growth period is characterized by at least a 3-day inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
101
1
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 6 publications
5
101
1
1
Order By: Relevance
“…A recent study by Hahn, Walters, and DeLuca (Note 2) found that 12-day-old animals are in a plateau rather than a spurt, as previously reported by Gottlieb et al (1977). We tested mice in a passive avoidance situation at 11, 15, and 19 days of age, since 11-and 19-day-old animals are in established spurts and 15-day-old animals are in an established plateau.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…A recent study by Hahn, Walters, and DeLuca (Note 2) found that 12-day-old animals are in a plateau rather than a spurt, as previously reported by Gottlieb et al (1977). We tested mice in a passive avoidance situation at 11, 15, and 19 days of age, since 11-and 19-day-old animals are in established spurts and 15-day-old animals are in an established plateau.…”
mentioning
confidence: 69%
“…Epstein (1979) has shown a stagewise growth in average brain weight, and he correlates these braingrowth stages with mind-growth stages, or Piaget's stages of intellectual development. He suggests that the normal course of human brain development is not a linear process but, rather, is characterized by specific stages of rapid and slow growth, or spurts and plateaus, respectively.A study by Gottlieb, Keydar, and Epstein (1977) on mouse and rat brain growth from birth to weaning shows rapid growth (spurts) at 0-6, 8-12 or 13, and 17-23 days, and slow growth (plateaus) at 6-8,12-17, and after 23 days of age. Epstein's (1979) work predicts a decrement in learning ability at a plateau and increased learning in a spurt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we evaluated the effectiveness of DZP and PTB in stopping 1-hour long SE induced either by kainic acid (KA) or lithium-pilocarpine (Li-Pilo) in developing male rats at postnatal day (P)9, 15 and 21 which may correspond to a newborn (14)(15)(16)(17), toddler (18) and young child respectively (19,20). KA is a glutamate receptor agonist and pilocarpine is a muscarinic acetylcholine receptor agonist; both agents induce a partial onset SE with secondary generalization.…”
Section: Introductionmentioning
confidence: 99%
“…During the postnatal period rodents present three stages of rapid brain growth (4) in which they are especially prone to neurotoxicants (5,6). However, there are few studies in the literature concerning the effects of lead on specific stages of postnatal brain development (6).…”
mentioning
confidence: 99%